Comprehensive patient education and counselling for non-communicable diseases in primary care, Western Cape - Robert J. Mash; Joleen Cairncross (South African Family Practice)
Background: Treatment of non-communicable diseases (NCD) requires patient education and counselling (PEC). Initiatives have focused on Group Empowerment and Training (GREAT) for diabetes and Brief behaviour change counselling (BBCC). However, the implementation of comprehensive PEC in primary care remains a challenge. The aim of this study was to explore how such PEC could be implemented.